MEMBANGUN INTERAKSI DAN KOMUNIKASI INTERPERSONAL YANG EFEKTIF : KOMPETENSI HUMAS BERKOMUNIKASI DI FACEBOOK - Fazil - (UNIVED PRESS, Universitas Dehasen Bengkulu, 2014)
Retrieved from kominfo.go.id, the Director of Information Services of International Directorate General of Public Information and Communication, Selamatta Sembiring, said that 95 % of internet users accesses social networking sites. The most accessible social networking sites are Facebook and Twitter. This research uses descriptive qualitative approach by using methods which are data collection, interview, and documentation. The interaction in interpersonal communication on Facebook tends to be similar to the daily interpersonal communication. Both of them have similar steps of daily interpersonal communication process as proposed by Devito (1997:233) which are contact, involvement, familiarity, destruction, and termination. The next development is that the connectivity among Facebook users is no longer based on known people who live far away. Facebook expands the reach of connectedness based on specific needs of humans. As shown on the early development of Facebook, that connection is expanded on university students. It can be seen from the specific need of university students that is the need of educational information. The existence of new media, especially Facebook, cannot be underestimated by public relations. It can be a chance to optimize its role and its function internally and externally or publicly. The existence of new media repositions public affairs function which tends to be closed and one-way communication to be open and two-way communication. This new situation requires public relations to have the appropriate interaction competence in the public as well as effective interpersonal communication on social media, especially Facebook. Keywords : interpersonal communication, public information and communication, facebook